PENGARUH INFORMASI AKUNTANSI TERHADAP HARGA SAHAM - mokoginta, dirgantara dahana (Universitas Dharmawangsa, 2025)
This study aims to analyze the effect of accounting information, consisting of profitability, firm size, and leverage, on stock prices of companies listed in the LQ45 index on the Indonesia Stock Exchange between 2022-2024. The results show that profitability and leverage have no significant effect on stock prices, while firm size has a positive effect. These findings indicate that investors in the Indonesian capital market, particularly those investing in companies listed in the LQ45 index, tend to pay more attention to the firm size factor rather than to accounting indicators such as profitability and leverage.